Diagnostic and pathogenic features of calcifying pseudoneoplasm of the neuraxis. (May 2021) - Yang, K; Reddy, K; Wang, BH; Cenic, A; Ang, LC; Provias, J; Yong, WH; Lu, JQ
Abstract : Calcifying pseudoneoplasm of the neuraxis (CAPNON) is a rare tumefactive lesion with unclear pathogenesis. It is diagnosed by pathological findings of the typical histological features that include granular amorphous cores with palisading spindle to epithelioid cells, variable fibrous stroma, foreign-body reaction with giant cells, and calcification/ossification occasionally with psammoma bodies. However, its histopathology may be variable and currently immunohistochemistry plays a limited role in its diagnosis and understanding the pathogenesis. In this study, we examined 6 cases of CAPNONs including 3 intracranial and 3 spinal epidural lesions (age range: 59–69 years; 3 males and 3 females). Immunohistochemistry revealed that all CAPNON cores contain abundant positive deposits of neurofilament protein (NFP), which was supported by electron microscopy finding of filaments (8–13 nm in diameter). In comparison, no NFP positivity was found in 5 psammomatous/metaplastic meningiomas or 7 intervertebral tissue lesions with calcification/ossification. In addition, CAPNON cellular areas showed variable numbers of CD8+ cytotoxic T-cells with less CD4+ T-cells and a decreased ratio of CD4/CD8+ cells, versus the intervertebral tissue lesions without CD8+ or CD4+ cells. Our findings suggest that NFP may be a principal constituent of CAPNONs, and thus involved in the pathogenesis of CAPNON. Given the decreased CD4/CD8 ratio, the pathogenic process of CAPNON is possibly immune- mediated. LEARNING OBJECTIVES: The presentation will enable the learner to: 1. Discuss histopathological features of calcifying pseudoneoplasm of the neuraxis (CAPNON) with variation of non-core components. 2. Explore diagnostic and pathogenic roles of immunohistochemical markers including neurofilament protein and CD4/CD8 in CAPNON.